Moments of IV and JIVE Estimators - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 2006)
We develop a new method, based on the use of polar coordinates, to investigate the existence of moments for instrumental variables and related estimators in the linear regression model. For generalized IV estimators, we obtain familiar results. For JIVE, we obtain the new result that this estimator has no moments at all. Simulation results illustrate the consequences of its lack of moments.
Keywords: C10; C13; 330; polar coordinates; simultaneous equations; JIVE; moments; instrumental variables